PETROLOGIE ET GEOCHIMIE DES RHYOLITES D’AÏN SEDMA-COLLO (NE ALGERIEN) : ESSAI D’UN MODELE PETRO GENETIQUE - LAKKAICHI, A.; BOUABSA, L. (Courrier du Savoir, 2017)
ABSTRACT The purpose of this work is to determine the characteristics and petrogeochemical changes for the rhyolites of Ain Sedma NE Algeria Collo. The study area is located at 11 kms northwest of the city of Collo. Geologically speaking this complex consists of four rock types: rhyolites, granites, microgranodiorite and microgranites. From petrography point of view, this rhyolite shows two types of texture, spherolitic hyaline texture and the other is microlitic porphyritic with dolerite trend. Its Mineralogy is relatively constant; it is mainly composed of spherulitic quartz, plagioclase (andesine), orthose, biotite and rarely muscovite, chlorite and epidote. geochemically this rhyolite shows a high proportion of SiO2, a low Na2O content compared to that of K2O and belongs to the hyper-potassium calc alkaline series and shows a peraluminous character. Trace geochemistry and rare earths combined with geotectonic discrimination diagrams show that these rocks originate in a continental crust during the collision stage, from a source of LREE enriched mafic magmas originating from the metasomatized lithospheric mantle during subduction , These magmas then evolved by fractional crystallization and crustal contamination according to the Melting-Assimilation-Storage-Homogeneization (MASH) model in the fourth phase to form the felsic vein rocks in the sector of Ain Sedma and NW of Cape Bougaroun.